2023
DOI: 10.3390/ijms24010830
|View full text |Cite
|
Sign up to set email alerts
|

Chinese Pedigree with Hereditary Gastrointestinal Stromal Tumors: A Case Report and Literature Review

Abstract: Familial gastrointestinal stromal tumor (GIST) is a rare autosomal dominant genetic disorder with only a few affected families reported to date. Here, we report a case of familial GISTs harboring a novel germline mutation within exon 18 of KIT. A 58-year-old male patient presented with gastric subepithelial lesions accompanied by cutaneous hyperpigmentation, which were subsequently diagnosed as multinodular GISTs. Endoscopic surgery was initially conducted to remove the larger lesions, and pathological examina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…A recent study reported a germline mutation case of KIT exon 18 A829P with primary resistance to imatinib. 20 In sporadic GIST, A829P is commonly found in secondary resistant mutations after imatinib treatment. These reports suggest that germline mutations in GISTs may share similar TKI sensitivity with somatic mutations.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study reported a germline mutation case of KIT exon 18 A829P with primary resistance to imatinib. 20 In sporadic GIST, A829P is commonly found in secondary resistant mutations after imatinib treatment. These reports suggest that germline mutations in GISTs may share similar TKI sensitivity with somatic mutations.…”
Section: Discussionmentioning
confidence: 99%